Solid Waste Management Optimization Techniques: A Systematic Review - Imman Khalid; Imran Shafi; Jamil Ahmad; Tahir Khurshaid; Muhammad Shafiq; Imran Ashraf (International Journal of Environmental Research, 2026)

Regulatory roles of miRNAs in development and progression of Hepatocellular carcinoma - Yasmeen Ishaq; Bisma Rauff; Muhammad Rehan Chaudhry; Mohamad S. Hakim; Sana Khurshid; Shafiq Ahmad Chudhary; Aqsa Ikram (Molecular Biology Reports, 2026)

Longitudinal genomic insights into resistance and virulence dynamics of Klebsiella pneumoniae clinical isolates from Pakistan - Wazeer Muhammed Abdullah; Iqbal Ahmad Alvi; Saba Sana; Shafiq-ur-Rehman; Muhammad Asif (Brazilian Journal of Microbiology, 2026)

From commensal to pathobiont: The emergence of virulence-enhanced Escherichia coli in China's food-animal systems – insights with future implications - Nishant Shah; Asim Munir; Muhammad Shafiq; Muhammad Shoaib (Food Research International, 2026)

Numerical analysis of Soret and Dufour effects in chemically reactive bioconvective flow through a converging–diverging channel - Muhammad Naveed Khan; Karim Choubani; Shafiq Ahmad; Hongchu Chen; Mohammed A. Almeshaal (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Comparative metagenomic analysis of two contrasting untreated wastewater systems in Morocco reveals site-specific resistome–mobilome patterns and detects last-resort resistance genes - Habiba Raqraq; Muhammad Shafiq; Amina Ressmi; Rafik Aniba; Assmaa Dihmane; Jihane Fathi; Bahija El Goundali; Mohamed Bennani; Abouddihaj Barguigua (Journal of Environmental Chemical Engineering, 2026)

Development and Characterization of Proliposomes for Sustained Oral Delivery of the DPP-4 Inhibitor Vildagliptin - Shazia Ashraf; Asadullah Madni; Faizan Akram; Muhammad Farhan Hanif; Afifa Shafiq; Iqra Fatima Ayub (Journal of Pharmaceutical Innovation, 2026)

Antagonistic and synergistic interactions between Bacillus and Pseudomonas in the rhizosphere: Mechanistic basis, ecological constraints, and applications in plant growth promotion and disease suppression - Muhammad Mubeen; Bushra Mumtaz; Muhammad Umar Shafiq; Phyu Shin Thant; Tahir Mahmood; Muhammad Arslan Mushtaq; Sazada Siddiqui; Faisal Zulfiqar; Anam Moosa (Physiological and Molecular Plant Pathology, 2026)

Harnessing the biocontrol potential of Trichoderma: Mechanisms, applications, and future prospects in sustainable crop protection - Muhammad Faiq Irfan; Amjad Ali; Rabia Noor; Aniqa Ijaz; Hamza Rafiq; Faisal Shafiq Mirza (Physiological and Molecular Plant Pathology, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

The dual role of polyethylene glycol-simulated drought stress in Stevia rebaudiana (Bertoni): growth reduction and integrated physiological, biochemical, and steviol glycoside responses - Shafiq Hussain; Mehran Ali; Muhammad Zahid; Simone Ribeiro Lucho; Caroline Dambroz; Joyce Dória (Physiology and Molecular Biology of Plants, 2026)
Stevia rebaudiana Bertoni is a globally recognized natural sweetener owing to its zero-calorie steviol glycosides (SGs). However, drought stress, one of the leading abiotic constraints to crop productivity, adversely affects stevia growth and development, while simultaneously altering its biochemical composition. This review highlights the impact of polyethylene glycol (PEG)-induced drought stress on stevia, with particular emphasis on agronomic traits, metabolites, antioxidant activities, and SGs biosynthesis. PEG-mediated stress reduces key growth parameters, such as plant height, biomass, and leaf area, but in some cases, it promotes root elongation as an adaptive strategy to optimize water uptake. Such alterations are accompanied by biochemical adjustments, notably the up-regulation of antioxidant enzymes, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), which neutralize reactive oxygen species (ROS)-induced oxidative stress. Moreover, PEG stress enhances the accumulation of secondary metabolites, such as phenolic, flavonoids and terpenoids, thereby improving antioxidant potential and stress tolerance. Notably, PEG-induced drought stress shapes SG biosynthesis through the up-regulation of the methylerythritol phosphate (MEP) pathway and the differential expression of key SG-related genes. Such modulation frequently increases SG accumulation, thereby strengthening their medicinal and economic value. Overall, this review covers the dual nature of PEG-induced drought stress: while limiting agronomic performance, enhances SGs biosynthesis and antioxidant capacity. Gaining insights into these mechanisms will facilitate the development of optimized cultivation strategies under water deficit conditions. Future research should prioritize molecular breeding and advanced biotechnological approaches to enhance drought tolerance and maximize the production of bioactive metabolites in stevia.

Comparative identification of abiotic stress-responsive differentially expressed genes in chickpea using unsupervised machine learning, and traditional meta-analysis - Mohammad Shafiq; Rimshah Sabir; Yossma Waheed; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Genes & Genomics, 2026)

Single-ligation approach for construction of agroinfectious clone of single stranded DNA viruses - Muhammad Shafiq Shahid (Indian Phytopathology, 2026)

Dairy farm waste as a source of novel and globally disseminated multidrug-resistant Escherichia coli clones: A genomic and phylogeographic study - Muhammad Shoaib; Minjia Tang; Asim Munir; Muhammad Shafiq; Mashkoor Mohsin; Xuejing Zhang; Zhongyong Wu; Zhuolin He; Baocheng Hao; Shengyi Wang; Ruichao Li; Wanxia Pu (Journal of Hazardous Materials, 2026)

Antimicrobial peptides in shrimp aquaculture: Mechanisms, translational applications, and future perspectives - Muhammad Shafiq; Sardar Ali; Liaqat Zeb (Fish & Shellfish Immunology, 2026)

Artificial Intelligence-assisted Discovery of Novel Bilastine and Bepotastine Analogs Against the Histamine H1 Receptor: Integrated Molecular Dynamics and MM/PBSA Evaluation - Muhammad Husnain; Shabbir Muhammad; Shamsa Bibi; Shafiq ur Rehman; Abdullah G. Al-Sehemi; Shimmaa Mansour Moustafa Mohamed; Saleh S. Alarfaji (Journal of Pharmaceutical Innovation, 2026)

Dihydroxyflavones as potential therapeutic agents against inflammation and renal injury via p38 MAP kinase inhibition: an in silico and experimental study - Farwa Naqvi; Almas Jabeen; Muhammad Shafiq; Shaheen Faizi; Zaheer Ul-Haq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metagenomic surveillance identifies a high-risk antibiotic resistance profile in community wastewater: a pilot study from Pakistan - Ishaq Khan; Ihtisham Naeem; Shujait Ali; Mahnoor Gulbin; Arshad Iqbal; Muhammad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

Advances in Coated Fertilizers for Sustainable Agriculture - Muhammad Tahir Murad; Sadia Murad; Waqar Akram; Mohammad Shafiq u Rahman; Afroz Rais; Abdul Qadir; Dawood Atta (Journal of Soil Science and Plant Nutrition, 2026)

Influence of Planting Depth Combined with ZnSO₄ and FeSO₄ on Yield and Starch Quality of Six Potato Cultivars - Harrem Khalid; Muhammad Shafiq; Muhammad Rizwan Tariq; Zain Mushtaq; Maryam Saeed (Potato Research, 2026)

Endocrine-disrupting chemicals in aquatic ecosystems and their impacts on aquatic organisms and humans with advances in detection and remediation - Tariq Dildar; Yongcheng Xue; Wenxiao Cui; Mhd Ikhwanuddin; Muhammad Shafiq; Hongyu Ma (Journal of Zhejiang University-SCIENCE B, 2026)

Towards sustainable development: the synergistic impact of economic complexity, environmental regulation, and renewable energy on environmental performance in G20 economies - Xiuyun Yang; Muhammad Nouman Shafiq; Seemab Gillani (International Environmental Agreements: Politics, Law and Economics, 2026)

Mycoviruses against plant pathogenic fungi: current understanding and future avenues of their potential implication - Fatima Mukhtar; Noor Fatima; Sawera Manzoor; Iqbal Ahmad Alvi; Shafiq ur Rehman; Muhammad Asif (Archives of Microbiology, 2026)

CRISPR–anti-CRISPR dynamics: evolutionary, ecological and biotechnological perspectives - Javeria Idrees; Abdul Qadeer Shabbir; Iqbal Ahmad Alvi; Saba Sana; Shafiq ur Rehman; Muhammad Asif (Archives of Microbiology, 2026)

Genome-Wide Identification of Bax Inhibitor (BI) Gene in Potato (Solanum tuberosum) and Response During Begomovirus Infection - Saman Shahid; Riffat Siddique; Muhammad Shafiq; Heba I. Mohamed (American Journal of Potato Research, 2026)

Divergent physiological and biochemical strategies confer differential salinity and drought tolerance in five prevalent summer weeds - Saira Shafiq; Muhammad Zia Ul Haq; Muhammad Shahbaz; Iftikhar Ali (Biologia Futura, 2026)

Evaluating Lemna minor for bioethanol production and bioremediation of petrochemical wastewater - Fozia Shafiq; Ihsan ud din; Arif Ali Khattak; Muhammad Afzal (Biomass and Bioenergy, 2026)

Stem Cells and their Key Derivatives in Degenerative Musculoskeletal Diseases - Nawaz Khan; Zeynab Ahmadova; Bin Zeng; Waqas Ahmed; Tayyab Shafiq; Zihao Zhang; Aiyuan Su; Nazim Muhammad; Sajid Khan; Yujie Liang; Li Duan (Stem Cell Reviews and Reports, 2026)

Antimicrobial Potential and Genomic Insights of Novel Klebsiella Phage SBP against K-112 Serotype - Muhammad Asif; Iqbal Ahmad Alvi; Sibgha; Muhammad Luqman Qadir; Shafiq-ur-Rehman (Current Microbiology, 2026)

In-silico screening of anti-cancer natural compounds targeting NF-κB as identification of potential therapeutic inhibitor - Jarin Tasnim; Md. Mehedi Hasan; Qandeel Fatima; Laiba Rashid; Sarnop Sarker; Khan Rajib Hossain; Mamoona Nisar; Md. Tamzid Hossain Molla; Muhammad Imtiaz Shafiq; Mohammad Taufiq Alam (In Silico Pharmacology, 2026)

Sustainable nanocomposite-integrated polysulfone membranes with tunable surface charge and enhanced adsorptive capacity for heavy metal ions removal from wastewater - Abdullah Arshad; Muhammad Shozab Mehdi; Shafiq Uz Zaman; Saif-ur-Rehman (Chemical Engineering Journal, 2026)

Investigation of heat and mass transfer in an electromagnetically driven ionized tri-hybrid nanofluids flow over a convectively heated cylinder - Muhammad Naveed Khan; Shafiq Ahmad; Aamir Abbas Khan; Mounirah Areshi; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Regulation of biochemical attributes, photosynthetic pigments, and antioxidant activity in Zea mays L. for complete amelioration of heavy metal toxicity using synergistic application of arsenic-tolerant PGPR and nanoparticles - Mohsin Zafar; Humaira Yasmin; Tayyab Shafiq; Rabia Naz; Asia Nosheen; Muhammad Nadeem Hassan (Environmental Science and Pollution Research, 2026)

Fiscal and monetary policy for green growth: the role of institutional quality in South Asia - Rabia Nazir; Seemab Gillani; Muhammad Nouman Shafiq; Muhammad Junaid Nasrullah; Muhammad Faisal Shahzad (Environment, Development and Sustainability, 2026)

Phytochemical Profiling and Evaluation of the Anti-inflammatory and Antinociceptive Effects of Lilium polyphyllum Bulb Using In Silico, In Vitro and In Vivo Models - Haider Ali; Shafiq Ur Rahman; Umair Sayad; Atif Ali Khan Khalil; Muzaffar Abbas; Muhammad Shahid (Journal of Pharmaceutical Innovation, 2026)

Leachate arising from tannery solid waste open dump and its safety and productivity threats to food crops in adjoining agricultural fields - Muhammad Shafiq; Tasmia Maqbool; Aisha Nazir (Environmental Geochemistry and Health, 2026)

Evaluating synergistic toxicology effects of mixed microplastics on marine micro crustacean Artemia salina - Mariam Ali; Hira Amjad; Imran Hashmi; Hassan Shafiq; Noreddine Ghaffour; Muhammad Saqib Nawaz (Regional Studies in Marine Science, 2026)

Hierarchically structured fiber scaffold incorporating functionalized microspheres for sustained drug release and treatment of infected wounds - Hao Feng; Gonghao Zhang; Sidong Zhang; Lu Han; Zhengchao Yuan; Xiao Yu; Shuqi Lou; Yunhan Ji; Muhammad Shafiq; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Xiumei Mo; et al. (Chemical Engineering Journal, 2026)

Investigation of N-desmethyl-acetamiprid-induced neurotransmitter disturbances in cerebrospinal fluid from leukemia patients - Mengya Si; Muhammad Nadeem Khan; Hazrat Bilal; Muhammad Shafiq; Sabir Khan; Xiaoling Guo; Meimei Wang; Jilong Wu; Wang Zhen; Fen Yao; Adela Jing Li; Xiaoyang Jiao (Environmental Toxicology and Pharmacology, 2025)

Energy transport in ternary hybrid nanofluid with variable thermal conductivity under the combined effects of electroviscous, electric potential, and heat generation - Shafiq Ahmad; Aamir Abbas Khan; Muhammad Naveed Khan; Salah Knani; N. Ameer Ahammad; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2025)

Collateral damage of neonicotinoid insecticides: Unintended effects on gut microbiota of non-target organisms - Muhammad Nadeem Khan; Hazrat Bilal; Sabir Khan; Muhammad Shafiq; Xiaoyang Jiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Beta-Glucan in barley as a natural immunomodulator: mechanisms and therapeutic potential - Hafiz Ghulam Muhu Din Ahmed; Li’E Yang; Xiaomeng Yang; Jiazhen Yang; Sajid Hussain; Muhammad Danial Shafiq; Muhammad Irfan Akram; Muhammad Sajad; Yawen Zeng (Molecular Biology Reports, 2025)

Prevalence of New Delhi Metallo-β-lactamase (blaNDM) gene in a selected population of drug-resistant clinical isolates - Muhammad Shafiq; Aftab Ahmad; Kunza Latif; Muhammad Saeed; Iftikhar Ahmed; Muhammad Zeeshan Hyder (Molecular Biology Reports, 2025)

In vitro and In Vivo Antimicrobial Activity of Melia Azedarach-Mediated Copper Oxide Nanoparticles Against Multidrug-Resistant Klebsiella pneumoniae - Nimra Arshad; Mohsin Tassawar Cheema; Aatif Amin; Rida Fatima; Mounir M. Bekhit; Nady K. Elbarbary; Muhammad Shafiq; Mohsin Khurshid (Current Microbiology, 2025)

Comprehensive transcriptomic analysis of myostatin-knockout pigs: insights into muscle growth and lipid metabolism - Nasar Khan; Zhouyan Li; Akbar Ali; Biaohu Quan; Jindan Kang; Munib Ullah; Xi-Jun Yin; Muhammad Shafiq (Transgenic Research, 2025)

Microplastic Pollution: Sources, Degradation Mechanisms, Analytical Advances, and Mitigation Strategies for Environmental Sustainability - Najwa Ibrahim; Amir Muhammad Noh Amin Abdul Rahman; Mohamad Danial Shafiq; Zainovia Lockman; Mariatti Jaafar; Yutaka Kameda (Reviews of Environmental Contamination and Toxicology, 2025)

Fungal biopolymers in 3D bioprinting: Current status, challenges and future advancements - Muhammad Shafiq; Liaqat Zeb; Bin Xue; Yanjun Wan; Zhang Wen; Yajun Wang (Chemical Engineering Journal, 2025)

PM2.5 pollution and its correlation with meteorological parameters over the four capital cities of Pakistan - Bahadar Zeb; Jawad Nasir; Khan Alam; Allah Ditta; Muhammad Arif Aman; Muhammad Shafiq (Environmental Monitoring and Assessment, 2025)

Spatio-temporal variability study of Shigar Basin Glaciers, Central Karakoram Region, Pakistan - Salman Mustafa; Faisal Rehman; Adnan Shafiq Rana; Tahir Azeem; Omar Riaz; Muhammad Fahad Ullah; Jamil Siddique; Faisal Rehman (Environmental Monitoring and Assessment, 2025)

Retraction notice to “Recent advancement challenges with synthesis of biocompatible hemodialysis membranes” [Chemosphere 307, November 2022, 135626] - Shafiq Uz Zaman; Sikander Rafiq; Abulhassan Ali; Muhammad Shozab Mehdi; Amber Arshad; Saif-ur Rehman; Nawshad Muhammad; Muhammad Irfan; Muhammad Shahzad Khurram; Muhammad Khaliq U. Zaman; Abdulkader S. Hanbazazah; Hooi Ren Lim; et al. (Chemosphere, 2025)

Advancements in sustainable extraction of seaweed phenolics: Integrating extraction technologies with natural deep eutectic solvents (NADES) - Liaqat Zeb; Muhammad Shafiq; Monica Jordheim (Food Chemistry, 2025)

Mechanistic insights of facile synthesized-solar driven TiO2 intercalated 2D molybdenum disulfide evaporator for one-pot clean water production - Nurul Syazana Fuzil; Nur Hashimah Alias; Nur Hidayati Othman; Muhammad Shafiq Mat Shayuti; Norazah Abd Rahman; Zulkifli Abdul Rashid; Ahmad Fauzi Ismail; Anwar Ul-Hamid; Izumi Ichinose (Desalination, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Comparative Efficacy of Different Rice (Oryza sativa L.) Genotypes for Improved Zinc and Iron Uptake and Relevant Yield Efficiency under their Foliar Application - Shafiq ur Rahman Memon; Saima Parveen Memon; Muhammad Qasim; Huagang Huang; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Rashid Iqbal; Zicheng Zheng (Journal of Soil Science and Plant Nutrition, 2025)

Computational exploration of aphrodisiac potential: identifying inhibitors from Tribulus terrestris L., and Securidaca longepedunculata targeting human phosphodiesterase 5 - Sikiru Akinyeye Ahmed; Ali Agaka Aremu; Muhammad Shafiq; Zaheer Ul-Haq (In Silico Pharmacology, 2025)

In Silico and In Vitro Analysis of Bioactive Compounds from Ficus benghalensis as a Novel Approach to Targeting Brain Abscess Pathogen - Ihtesham Arshad; Maryum Zainab; Ayesha Farooq; Saira Zulfiqar; Anna Ali; Rubina Bibi; Shaista Shafiq; Imran Zafar; Muhammad Mazhar Ayaz; Yahya A. Almutawif; Najeeb Ullah Khan (Cell Biochemistry and Biophysics, 2025)

Evaluation of chalcones as new glycogen phosphorylase inhibitors – an in-vitro and in-silico approach - Talal Ahmed Awad; Fatima Alfatih; Muhammad Shafiq; Mohnad Abdalla; Samia T. Al-Shouli; Amani Bashir; Maaweya E. Awadalla; Hassan A. Alhazmi; Mohammed Albratty; Hafiz A. Makeen; Asaad Khalid; Zaheer Ul-Haq (Natural Product Research, 2025)

Balancing well-being and environment: The moderating role of governance in sustainable development amid environmental degradation - Feng Wang; Seemab Gillani; Arshian Sharif; Muhammad Nouman Shafiq; Umar Farooq (Journal of Environmental Management, 2025)

Boron-doped silica/chitosan-based elastic three-dimensional sponge scaffold for bone regeneration - Zheng Lei; Chunchun Li; Zhengchao Yuan; Xinyi Wang; Guangfang Cai; Panpan Shang; Yue Zhao; Muhammad Rafique; Mohamed EL-Newehy; Meera Moydeen Adulhameed; Muhammad Shafiq; Liang Song; et al. (Carbohydrate Polymers, 2025)

Exploring the Role of Plant Growth-Promoting Bacteria in Biodegradation of Plastic: A Review - Haris Maqbool; Fazal Ur Rehman; Izhar Khan; Nadeem Ullah; Muhammad Anwar Sajad; Nazir Mohammad; Maria Kalsoom; Shafiq Ur Rehman; Muhammad Farooq Hussain Munis; Malka Saba; Hassan Javed Chaudhary (Water, Air, & Soil Pollution, 2025)

Meta-analysis of RNA-seq data of soybean under heat, water, and drought stresses - Mohammad Shafiq; Farrukh Azeem; Yossma Waheed; Igor Eduardovich Pamirsky; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Plant Biotechnology Reports, 2025)

Biotransformation of curcumin by Streptomyces sp. K1-18 isolated from mangrove soil - Nurul Iman Aminudin; Wan Muhammad Shafiq Wan Jaafar; Nurul Mehiran Shafikah Mohd Amin; Raudah Kamarul Baharin; Zaima Azira Zainal Abidin (Natural Product Research, 2025)

Land use, hydroclimate and damming influence organic carbon sedimentation in a flood pulse wetland, Malaysia - Suzanne McGowan; Jack H. Lacey; Stefan Engels; John Boyle; Charlotte Briddon; Melanie J. Leng; Heather L. Moorhouse; Virginia Panizzo; Muhammad Shafiq (Journal of Quaternary Science, 2025)
Water bodies located in floodplains and tropical forests are known to be important carbon stores, but many are subjected to intensive pressures from damming, land use and climate changes. Sedimentary records preserve long‐term archives for understanding how such changes affect the quantity and quality of carbon stores. We analysed sediment cores from seven sites across a flood‐pulse multi‐basin wetland, Tasik Chini in Peninsular Malaysia (for percentage LOI 550 , sediment density and spheroidal carbonaceous particles), and conducted more analyses on three 210 Pb‐dated cores (X‐ray fluorescence of elements, grain size analysis, carbon isotopes, C/N ratios, carotenoid pigments) to gain an understanding of the drivers of organic carbon accumulation rates (OCARs) since 1860 ce. The median OCAR of 85 g m −2 a −1 for the basin since 1945 ce was higher than in other floodplain and temperate lakes and in line with other tropical forest lakes. However, we found evidence for different mechanisms of OC deposition across the basin. In ‘autochthonous mode’, the site with minimal local land disturbance had lowest OCARs and OC was derived mainly from autochthonous production, which rose slightly around 1940 ce when regional land disturbance increased nutrient influx to the basin. The site with the most long‐term and intensive land disturbance through forest removal (1940s) and then conversion to rubber and oil palm farming (1980s) functioned mainly in ‘allochthonous mode’; that is, increases in OCARs after 1940 ce were driven by deposition of soil‐derived OC. The highest OCARs were in the basin that was converted to oil palm after the 1980s and had increased iron mining activity in the 2000s; because this site was located distal from the flood pulse and became increasingly hydrologically disconnected after a low rainfall period in the 1970s, the lake responded strongly in ‘autochthonous mode’, through encroachment of fringing swamp, the spread of benthic algae and macrophytes, and efficient sediment retention. Weir installation in 1995 ce raised water levels and increased lentic conditions, promoting autochthonous OC production and sedimentation across all basins. The long‐term fate of this more recently deposited OC remains uncertain because it is more labile. Overall Tasik Chini has responded strongly to land use changes since at least the 1940s, earlier than anticipated in this region of Southeast Asia, and the sedimentary proxies indicate large changes in the ecosystem function and capacity for C storage over the past ca. 80 years. Most of these shifts have increased OC accumulation by strengthening autochthonous production or allochthonous OC fluxes, but the implications for other aspects of the C cycle, including catchment soil C loss and greenhouse gas production, need to be accounted for when evaluating the overall impacts of land and hydrological disruption.

Decentralized municipal solid waste management system (DMSWMS) as an alternative to centralized MSWMS (CMSWMS) for HEIs based on case study of the University of the Punjab, Lahore, Pakistan - Sidra Shahid; Muhammad Shafiq; Firdaus-e-Bareen (Environmental Monitoring and Assessment, 2025)

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

Eco-friendly herbicide tolerance in maize (Zea mays Linn.) using moringa (Moringa oleifera Lam.) leaf extract - Hameed Ullah Khan; Muhammad Mudasar Aslam; Tahir Iqbal; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Muhammad Nauman Khan; Majid Iqbal; Alevcan Kaplan; Sarah Abdul Razak; Baber Ali; Muhammad Siddique Afridi; et al. (Acta Physiologiae Plantarum, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

Modelling assisted phytoextraction of heavy metals from tannery origin leachate - Faiza Yahya; Aisha Nazir; Shoaib Ahmad; Sarah Owdah Alomrani; Muhammad Shafiq; Firdaus e Bareen; Mohammed Ali Alshehri; Shafaqat Ali (Chemosphere, 2025)

Morphological profiling and DNA barcoding revealed genetic diversity and phylogeny of Mentha species cultivated in Pakistan - Ismara Naseem; Muhammad Azam Khan; Umer Habib; Rashid Mehmood Rana; Muhammad Qasim; Mona S. Alwahibi; Rizwana Khanum; Muhammad Shafiq; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Enhanced production of exopolysaccharide by Antrodia cinnamomea through batch feeding of tansglycocylated sugar mixture: Physicochemical properties, biotechnological application, and gut microbiota modulating potential - Muhammad Shafiq; Liaqat Zeb; Yajun Wang; Waqas Waqas; Sardar Ali; Tariq Dildar; Qiong-Qiong Yang; Ka-Hing Wong; Bo-Bo Zhang (Chemical Engineering Journal, 2025)

A Novel Optimized Vibration-based Energy Harvester for Leak Detection in Wall-mounted Water Pipelines - Muhammad Faizan Mysorewala; Mati-Ur-Rasool Ashraf Virk; Mujahid Naqeebuddin Syed; Abdul-Wahid Saif; Lahouari Cheded; Saifullah Shafiq; Karim Sattar (Water Resources Management, 2025)

A comprehensive review on phytochemistry, pharmacology, preclinical, and clinical trials of Cydonia oblonga - Tuba; Muhammad Ajaz Hussain; Gulzar Muhammad; Muhammad Arshad Raza; Adnan Ashraf; Muhammad Tahir Haseeb; Muhammad Mushtaq; Zahid Shafiq (Phytochemistry Reviews, 2025)

Integrated Weed Management in Sunflower Using a Hybrid Mixture and Reduced Herbicide Dose - Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Shahid Ibni Zamir; Amina Shahbaz; Muhammad Saqib (Journal of Crop Health, 2025)

The role of agricultural land management in modulating water-carbon interplay within dryland ecological systems - Wajid Ali Khattak; Jianfan Sun; Fawad Zaman; Abdul Jalal; Muhammad Shafiq; Sehrish Manan; Rashida Hameed; Ihtisham Khan; Irfan Ullah Khan; Khalid Ali Khan; Daolin Du (Agriculture, Ecosystems & Environment, 2025)

Molecular characterization of chilli leaf curl virus and ‘Candidatus Phytoplasma trifolii’ infecting Capsicum annuum, India - Vineeta Pandey; Aarshi Srivastava; Smriti Mall; Ramwant Gupta; Abdullah M. Al-Sadi; Rakesh Kumar Verma; Muhammad Shafiq Shahid; R. K. Gaur (Vegetos, 2025)

Implications of Microalgal–Bacterial Interactions in Modern Aquaculture Practices: A Review of the Current Knowledge - Sardar Ali; Waqas Waqas; Md. Akibul Hasan Bakky; Sahib Zada; Uddin Md Saif; Md Tawheed Hasan; Muhammad Shafiq; Tariq Dildar; Wang Hui (Reviews in Aquaculture, 2025)
Microalgae play a crucial role in aquaculture due to their nutritional value and antimicrobial properties, yet harvesting them can be energy intensive. To address this, microalgal–bacterial interactions have emerged as a sustainable approach, enhancing growth rates and wastewater treatment efficiency but also significantly improve nutrient cycling, particularly through the removal of ammonia and phosphorus. These interactions range from mutualism to antagonism, influencing nutrient exchange and ecological niche formation. Despite their potential, the integration of bacterial–microalgal consortia remains limited in aquaculture. This review aims to expand understanding of these interactions, their benefits, and their role in optimizing aquaculture systems. Various aspects of microalgae–bacterial interactions, including mutualistic and commensal relationships, antibiotics production by algae, and the algicidal role of bacteria, are discussed. Factors influencing these interactions, such as nutrient availability, the physical environment, chemical signaling, and microbial community composition, are also explored. The potential effects of microalgae–bacterial interactions on aquaculture, including enhanced revenue, efficiency, and ecological sustainability, are highlighted. Further research is needed to identify bacterial groups' influence on microalgal output and their potential for enhancing productivity in commercial aquaculture systems. Understanding and leveraging these microbial interactions could significantly improve aquaculture practices.

Improving green innovation performance: the role of integrating green customers and suppliers, government regulations, green knowledge integration capability - Sami Ullah; Tooba Ahmad; Muhammad Shafiq; Tariq Mehmood; Mohit Kukreti; Muhammad Rehan Shaukat (Environment, Development and Sustainability, 2024)

Health risk assessment of lead and cadmium exposure from food and snuff in Pakistani population - Hamza Shafiq; Mamoona Amir; Salman Asghar; Aneela Hameed; Muhammad Riaz (Journal of Trace Elements in Medicine and Biology, 2024)

Pre-emergence herbicide selection for successful cultivation of black seed (Nigella sativa L.), psyllium (Plantago ovata Forsk), and quinoa (Chenopodium quinoa Willd.) - Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Zia Ul Mohsin; Majid Ali; Abdul Khaliq; Rana Nadeem Abbas; Muhammad Zafar Iqbal; Amar Matloob (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Comparative assessment of pantothenic, aspartic, ascorbic and tartaric acids assisted Pb-phytoextraction by sunflower (Helianthus annuus L.) - Asif Ghafoor; Fahad Shafiq; Sumera Anwar; Lixin Zhang; Muhammad Ashraf (BioMetals, 2024)

Integrative metagenomic dissection of last-resort antibiotic resistance genes and mobile genetic elements in hospital wastewaters - Muhammad Shafiq; Xiaoling Guo; Meimei Wang; Hazrat Bilal; Li Xin; Yumeng Yuan; Fen Yao; Taha Majid Mahmood Sheikh; Muhammad Nadeem Khan; Xiaoyang Jiao (Science of The Total Environment, 2024)

Poly(L-lactide-co-ɛ-caprolactone)/gelatin-based small-diameter vascular grafts: Salutatory effect of the BVLD and EGCG-Cu to promote hemocompatibility and nitric oxide production for in situ blood vessel regeneration - Guangfang Cai; Zhengchao Yuan; Xinyi Wang; Siyuan Wu; Shasha Zhou; Zheng Lei; Peng Li; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Muhammad Shafiq; Xiumei Mo; Shichao Jiang; et al. (Chemical Engineering Journal, 2024)

Intercalation of GO-Ag nanoparticles in cellulose acetate nanofiltration mixed matrix membrane for efficient removal of chromium and cobalt ions from wastewater - Muhammad Hamad Zeeshan; Umm E. Ruman; Muhammad Shafiq; Sharjeel Waqas; Aneela Sabir (Journal of Environmental Chemical Engineering, 2024)

Salt-Tolerant Plant Growth-Promoting Bacteria (ST-PGPB): An Effective Strategy for Sustainable Food Production - Syeda Tahseen Zahra; Mohsin Tariq; Muhammad Abdullah; Muhammad Kaleem Ullah; Abdul Rafay Rafiq; Aisha Siddique; Muhammad Shafiq Shahid; Temoor Ahmed; Imrana Jamil (Current Microbiology, 2024)

Legume choice and planting configuration influence intercrop nutrient and yield gains through complementarity and selection effects in legume-based wheat intercropping systems - Muhammad Ali Raza; Atta Mohi Ud Din; Ghulam Abbas Shah; Wang Zhiqi; Ling Yang Feng; Hina Gul; Hassan Shehryar Yasin; Mohammad Shafiq ur Rahman; Chen Juan; Xue Liang; Raheela Rehman; Amal Mohamed Al Garawi; et al. (Agricultural Systems, 2024)

Health risk assessment of bread wheat grown under cadmium and nickel stress and impact of silicic acid application on its growth, physiology, and metal uptake - Alina Shafiq; Muhammad Emmad Munawar; Muhammad Nadeem; Asia Khan; Ghulam Hasan Abbasi; Muhammad Anwar ul Haq; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Quantification and polymeric characterization of microplastics in composts and their accumulation in lettuce - Aamna Naeem; Muhammad Ansar Farooq; Muhammad Shafiq; Muhammad Arshad; Aamir Alaud Din; Abdulrahman Ali Alazba (Chemosphere, 2024)

Multiomics analysis reveals a substantial decrease in nanoplastics uptake and associated impacts by nano zinc oxide in fragrant rice (Oryza sativa L.) - Muhammad Imran; Muhammad Junaid; Sarfraz Shafiq; Shulin Liu; Xiaoyuan Chen; Jun Wang; Xiangru Tang (Journal of Hazardous Materials, 2024)

A deep learning-based theoretical protocol to identify potentially isoform-selective PI3Kα inhibitors - Muhammad Shafiq; Zaid Anis Sherwani; Mamona Mushtaq; Mohammad Nur-e-Alam; Aftab Ahmad; Zaheer Ul-Haq (Molecular Diversity, 2024)

Enhancing drought tolerance in broccoli (Brassica oleracea L.) through melatonin application: Physiological and biochemical insights into growth, photosynthesis, and antioxidant defense mechanisms - Hasan Sardar; Muhammad Shafiq; Safina Naz; Sajid Ali; Riaz Ahmad; Shaghef Ejaz (Biocatalysis and Agricultural Biotechnology, 2024)

Integrated computational modeling and in-silico validation of flavonoids-Alliuocide G and Alliuocide A as therapeutic agents for their multi-target potential: Combination of molecular docking, MM-GBSA, ADMET and DFT analysis - Nusrat Shafiq; Misha Arshad; Awais Ali; Fatima Rida; Mohamed Mohany; Uzma Arshad; Muhammad Umar; Marija Milošević (South African Journal of Botany, 2024)

Plant-Derived Smoke Solution: A Stress Alleviator in Crop - Muhammad Mudasar Aslam; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Setsuko Komatsu (Journal of Plant Growth Regulation, 2024)

Toxic effects of heavy metals on crustaceans and associated health risks in humans: a review - Waqas Waqas; Ye Yuan; Sardar Ali; Mengqian Zhang; Muhammad Shafiq; Wajid Ali; Yongyi Chen; Zifei Xiang; Ruixiang Chen; Mhd Ikhwanuddin; Hongyu Ma (Environmental Chemistry Letters, 2024)

Genome-wide identification and in-silico expression analysis of CCO gene family in sunflower (Helianthus annuus) against abiotic stress - Adnan Sami; Muhammad Zeeshan Haider; Muhammad Shafiq; Saleh Sadiq; Farooq Ahmad (Plant Molecular Biology, 2024)
Carotenoid cleavage oxygenases (CCOs) enzymes play an important role in plant growth and development by producing a wide array of apocarotenoids and their derivatives. These compounds are vital for colouring flowers and fruits and synthesizing plant hormones such as abscisic acid and strigolactones. Despite their importance, the gene family responsible for CCO enzymes in sunflowers has not been identified. In this study, we identify the CCO genes of the sunflower plant to fill this knowledge gap. Phylogenetic and synteny analysis indicated that the Helianthus annuus CCO (HaCCO) genes were conserved in different plant species and they could be divided into three subgroups based on their conserved domains. Analysis using MEME tool and multiple sequence alignment identified conserved motifs in the HaCCO gene sequence. Cis -regulatory elements (CREs) analysis of the HaCCO genes indicated the presence of various responsive elements related to plant hormones, development, and responses to both biotic and abiotic stresses. This implies that these genes may respond to plant hormones, developmental cues, and drought stress, offering potential applications in the development of more resistant crops. Genes belonging to the 9-cis-epoxy carotenoid dioxygenases (NCED) subgroups predominantly exhibited chloroplast localization, whereas the genes found in other groups are primarily localized in the cytoplasm. These 21 identified HaCCOs were regulated by 60 miRNAs, indicating the crucial role of microRNAs in gene regulation in sunflowers. Gene expression analysis under drought stress revealed significant up-regulation of HaNCED16 and HaNCED19 , genes that are pivotal in ABA hormone biosynthesis. During organ-specific gene expression analysis, HaCCD12 and HaCCD20 genes exhibit higher activity in leaves, indicating a potential role in leaf pigmentation. This study provides a foundation for future research on the regulation and functions of the CCO gene family in sunflower and beyond. There is potential for developing molecular markers that could be employed in breeding programs to create new sunflower lines resistant to biotic and abiotic stresses.

Anti-inflammatory potential of some eudesmanolide and guaianolide sesquiterpenes - Shagufta Perveen; Azadeh Hamedi; Ardalan Pasdaran; Reza Heidari; Muhammad Shafiq ul Azam; Sobia Tabassum; Rashad Mehmood; Jiangnan Peng (Inflammopharmacology, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

SPOTLIGHT: NAC transcription factor elevates iron content in maize: A promising solution to combat iron deficiency - Muhammad Imran; Sarfraz Shafiq; Emilie Widemann (Journal of Plant Physiology, 2024)

Advancements in TiO2-based photocatalysis for environmental remediation: Strategies for enhancing visible-light-driven activity - Ruhma Rashid; Iqrash Shafiq; Muhammad Rehan Hasan Shah Gilani; Muhammad Maaz; Parveen Akhter; Murid Hussain; Kwang-Eun Jeong; Eilhann E. Kwon; Sungjun Bae; Young-Kwon Park (Chemosphere, 2024)

Integrated biorefinery approach for bioconversion of fish manure to volatile fatty acids and its valorization by Schizochytrium sp for docosahexaenoic acid, squalene, and carotenoids production - Muhammad Shafiq; Bo-Bo Zhang; Liaqat Zeb; Sardar Ali; Waqas Waqas; Muhammad Ayaz; Sartaj Ali; Zhanyou Chi (Journal of Water Process Engineering, 2024)

Modified carbon paste electrode with choline proline in enhancing the performance of water electrolysis system for hydrogen production - Muhammad Usman; Fakrul Shahril Ezanie Zulkefli; Mohd Dzul Hakim Wirzal; Shafiq M. Hizam; Aliya Nurzafira Nor Zaidi; Muhammad Syaamil Saad (Fuel, 2024)

Physiological and biochemical effects of biochar nanoparticles on spinach exposed to salinity and drought stresses - Aimun Rasheed; Sumera Anwar; Fahad Shafiq; Zaib-un-Nisa; Shahbaz Khan; Muhammad Ashraf (Environmental Science and Pollution Research, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Enhanced lead phytoextraction and soil health restoration through exogenous supply of organic ligands: Geochemical modeling” - Maria Manzoor; Muhammad Shafiq; Iram Gul; Usman Rauf Kamboh; Dong-Xing Guan; Abdulrahman Ali Alazba; Sven Tomforde; Muhammad Arshad (Journal of Environmental Management, 2023)

Revolutionizing wastewater treatment with microalgae: Unveiling resource recovery, mechanisms, challenges, and future possibilities - Hassimi Abu Hasan; Mohd Hafizuddin Muhamad; Bin Ji; Nur Aisyah Nazairi; Koh Weng Jiat; Saffi Irdina Sim Wan Azlan Sim; Amir Fitri Muhammad Shafiq Poh (Ecological Engineering, 2023)

Expression Studies of Synthetic Sucrose Isomerase Gene 1 (SySIG1) in Saccharum officinarum L - Mudassar Fareed Awan; Sajed Ali; Irfan Ullah; Amin Ullah; Muhammad Tariq; Muhammad Shahzad Iqbal; Aisha Khalid; Sana Fatima; Yousuf Shafiq; Idrees Ahmad Nasir; Muhammad Muzammal; Arshad Farid (Plant Molecular Biology Reporter, 2023)

Zinc oxide nanoparticles: biogenesis and applications against phytopathogens - Fazal ur Rehman; Najeeba Paree Paker; Shafiq ur Rehman; Muhammad Tariq Javed; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Journal of Plant Pathology, 2023)

Molecular characterization of azoreductase and its potential for the decolorization of Remazol Red R and Acid Blue 29 - Ghulam Mustafa; Muhammad Tariq Zahid; Mayur Bharat Kurade; Swapnil Mahadeo Patil; Farah Rauf Shakoori; Zeeshan Shafiq; Sidra Ihsan; Yongtae Ahn; Azmat Ali Khan; Amel Gacem; Byong-hun Jeon (Environmental Pollution, 2023)

Impact and mitigation of lead, cadmium and micro/nano plastics in fragrant rice - Muhammad Imran; Muhammad Ansar Farooq; Ayesha Batool; Sarfraz Shafiq; Muhammad Junaid; Jun Wang; Xiangru Tang (Environmental Pollution, 2023)

Cryopreservation protocol resolving the "temperature" challenges of long-distance transportation of Beetal buck (Capra hircus) sperm - Syed Aftab Hussain Shah; Muhammad Shafiq Haider; Hussain Ahmed; Muhammad Hammad Fayyaz; Syed Murtaza Hassan Andrabi (Small Ruminant Research, 2023)

Enhancement of combustion effect leading to improved performance and exhaust emissions of an SI engine with ferrous oxide and graphite nanoparticles - Yasir Hussain Siddiqui; Muhammad Shakaib; Adnan Rasheed; Hafiz Muhammad Ali; Syed Mohammad Rizwan Azeem; Athar Husain Siddique; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Influence of the chronic groundwater fluoride consumption on cholinergic enzymes, ACHE and BCHE gene SNPs and pro-inflammatory cytokines: A study with Pakistani population groups - Sara Bibi; Rabia Habib; Sania Shafiq; Syed Sayyam Abbas; Shaiza Khan; Syed Ali Musstjab Akber Shah Eqani; Eugenie Nepovimova; Mansoor Shaukat Khan; Kamil Kuca; Syed Muhammad Nurulain (Science of The Total Environment, 2023)

Bio-fabrication of zinc oxide nanoparticles from Picea smithiana and their potential antimicrobial activities against Xanthomonas campestris pv. Vesicatoria and Ralstonia solanacearum causing bacterial leaf spot and bacterial wilt in tomato - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Muhammad Naeem; Muhammad Farooq Hussain Munis; Shafiq ur Rehman; Hassan Javed Chaudhary (World Journal of Microbiology and Biotechnology, 2023)

Health risk assessment and bioaccumulation of potentially toxic metals from water, soil, and forages near coal mines of district Chakwal, Punjab, Pakistan - Nida Zainab; Shehzad Mehmood; Amna Shafiq-ur-Rehman; Adeela Munir; Zafar Iqbal Tanveer; Zaib Un Nisa; Muhammad Imran; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2023)

Recent progress on the heavy metals ameliorating potential of engineered nanomaterials in rice paddy: a comprehensive outlook on global food safety with nanotoxicitiy issues - Temoor Ahmed; Muhammad Noman; Muhammad Rizwan; Shafaqat Ali; Muhammad Shafiq Shahid; Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Entropy-based grid approach for handling outliers: a case study to environmental monitoring data - Anwar Shah; Bahar Ali; Fazal Wahab; Inam Ullah; Kassian T. T. Amesho; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Physiological effects of some engineered nanomaterials on radish (Raphanus sativus L.) intercropped with pea (Pisum sativum L.) - Mehr-un-Nisa; Fahad Shafiq; Sumera Anwar; Arslan Mahmood; Muhammad Iqbal; Kaleem Ullah; Muhammad Zulqarnain; Imtiaz Haider; Muhammad Ashraf; Lixin Zhang (Environmental Science and Pollution Research, 2023)

MoS2-TiO2 coated PVDF-based hollow fiber membranes for permeate flux enhancement in membrane distillation - Nurul Syazana Fuzil; Nur Hidayati Othman; Nur Hashimah Alias; Fauziah Marpani; Muhammad Shafiq Mat Shayuti; Munawar Zaman Shahruddin; Mohd Rizuan Mohd Razlan; Norazah Abd Rahman; Woei Jye Lau; Mohd Hafiz Dzarfan Othman; Ahmad Fauzi Ismail; Tutuk Djoko Kusworo; et al. (Journal of Environmental Chemical Engineering, 2023)

Metagenomic evidence for antibiotics-driven co-evolution of microbial community, resistome and mobilome in hospital sewage - Jiayu Sun; Yumeng Yuan; Leshan Cai; Mi Zeng; Xin Li; Fen Yao; Weidong Chen; Yuanchun Huang; Muhammad Shafiq; Qingdong Xie; Qiaoxin Zhang; Naikei Wong; et al. (Environmental Pollution, 2023)

Interactive Effects of Soil and Foliar-Applied Nanobiochar on Growth, Metabolites, and Nutrient Composition in Daucus carota - Habiba Khaliq; Sumera Anwar; Fahad Shafiq; Muhammad Ashraf; Lixin Zhang; Imtiaz Haider; Shahbaz Khan (Journal of Plant Growth Regulation, 2023)

Triladyl® improves the cryopreserved quality and in vivo fertilization potential of Beetal buck (Capra hircus) spermatozoa - Syed Aftab Hussain Shah; Muhammad Shafiq Haider; Hussain Ahmed; Muhammad Hammad Fayyaz; Syed Murtaza Hassan Andrabi (Small Ruminant Research, 2023)

Fullerenol [60] Nano-cages for Protection of Crops Against Oxidative Stress: A Critical Review - Fahad Shafiq; Muhammad Iqbal; Syed Hammad Raza; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Characterization of tomato leaf curl Palampur virus naturally infecting wild melon in Oman - Muhammad Shafiq Shahid (Indian Phytopathology, 2023)

Metagenomic insights into antibiotic resistance-related changes in microbial communities, resistome and mobilome under a modified A2/O treatment process for hospital sewage - Yumeng Yuan; Mi Zeng; Jiayu Sun; Xin Li; Fen Yao; Muhammad Shafiq; Xiaoling Guo; Meimei Wang; Tao Lu; Nai-Kei Wong; Adela Jing Li; Xiaoyang Jiao (Journal of Environmental Chemical Engineering, 2023)

Realizing direct and indirect impact of environmental regulations on pollution: A path analysis approach to explore the mediating role of green innovation in G7 economies - Rabia Nazir; Seemab Gillani; Muhammad Nouman Shafiq (Environmental Science and Pollution Research, 2023)

Polymeric Nanogel for Oral Delivery of the Chemotherapeutic Agent: Fabrication and Evaluation Alongside Toxicological Studies and Histopathological Examination - Humaira Sultana; Muhammad Naeem Aamir; Asadullah Madni; Masood ur Rehman; Afifa Shafiq; Jafir Hussain Shirazi; Sidra Hassan; Sumaira (AAPS PharmSciTech, 2023)

Deep learning-based marine big data fusion for ocean environment monitoring: Towards shape optimization and salient objects detection - Sulaiman Khan; Inam Ullah; Farhad Ali; Muhammad Shafiq; Yazeed Yasin Ghadi; Taejoon Kim (Frontiers in Marine Science, 2023)
Objective During the last few years, underwater object detection and marine resource utilization have gained significant attention from researchers and become active research hotspots in underwater image processing and analysis domains. This research study presents a data fusion-based method for underwater salient object detection and ocean environment monitoring by utilizing a deep model. Methodology A hybrid model consists of an upgraded AlexNet with Inception v-4 for salient object detection and ocean environment monitoring. For the categorization of spatial data, AlexNet is utilized, whereas Inception V-4 is employed for temporal data (environment monitoring). Moreover, we used preprocessing techniques before the classification task for underwater image enhancement, segmentation, noise and fog removal, restoration, and color constancy. Conclusion The Real-Time Underwater Image Enhancement (RUIE) dataset and the Marine Underwater Environment Database (MUED) dataset are used in this research project’s data fusion and experimental activities, respectively. Root mean square error (RMSE), computing usage, and accuracy are used to construct the model’s simulation results. The suggested model’s relevance form optimization and conspicuous item prediction issues in the seas is illustrated by the greatest accuracy of 95.7% and low RMSE value of 49 when compared to other baseline models.

Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red - Iqra Mahboob; Iqrash Shafiq; Sumeer Shafique; Parveen Akhter; Mamoona Munir; Muhammad Saeed; Muhammad Shahid Nazir; Um-e-Salma Amjad; Farrukh Jamil; Nabeel Ahmad; Young-Kwon Park; Murid Hussain (Chemosphere, 2023)

Ecological mechanisms of sedimental microbial biodiversity shift and the role of antimicrobial resistance genes in modulating microbial turnover - Okugbe Ebiotubo Ohore; Yuwen Wang; Yunjie Wei; Edmond Sanganyado; Muhammad Shafiq; Xiaoyang Jiao; Amechi S. Nwankwegu; Wenhua Liu; Zhen Wang (Journal of Environmental Management, 2023)

Nickel-based nitrodopamine MOF and its derived composites functionalized with multi-walled carbon nanotubes for efficient OER applications - Sonia Kiran; Ghazala Yasmeen; Zahid Shafiq; Amir Abbas; Sumaira Manzoor; Dilshad Hussain; Rami Adel Pashameah; Eman Alzahrani; Abdullah K. Alanazi; Muhammad Naeem Ashiq (Fuel, 2023)

Nitrogen-rich three-dimensional metal-organic framework microrods as an efficient electrocatalyst for oxygen evolution reaction and supercapacitor applications - Muhammad Imran Anwar; Sumaira Manzoor; Limin Ma; Muhammad Asad; Wenhua Zhang; Zahid Shafiq; Muhammad Naeem Ashiq; Guang Yang (Fuel, 2023)

Exploring antibiotic resistance genes, mobile gene elements, and virulence gene factors in an urban freshwater samples using metagenomic analysis - Sohail M. Noman; Muhammad Shafiq; Shabana Bibi; Bharti Mittal; Yumeng Yuan; Mi Zeng; Xin Li; Oluwaseyi Abraham Olawale; Xiaoyang Jiao; Muhammad Irshad (Environmental Science and Pollution Research, 2023)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Economic policy uncertainty and environmental degradation: the moderating role of political stability - Umar Farooq; Seemab Gillani; Bilal Haider Subhani; Muhammad Nouman Shafiq (Environmental Science and Pollution Research, 2022)

Biosorption potential and molecular characterization of metal-resistant autochthonous microbes from tannery solid waste - Hajira Younas; Aisha Nazir; Zakia Latif; Janice E. Thies; Muhammad Shafiq; Firdaus-e- Bareen (Archives of Microbiology, 2022)

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Relational pre-impact assessment of conventional housing features and carbon footprint for achieving sustainable built environment - Syed Shujaa Safdar Gardezi; Nasir Shafiq; Muhammad Waris Ali Khan (Environment, Development and Sustainability, 2022)

Scholarly output of energy and fuels research in Saudi Arabia during 1972–2020: a bibliometric analysis - Mohammad Aqil; Muhammad Abdul Mujeebu; Shafiq Ur Rehman; Shakil Ahmad (Arabian Journal of Geosciences, 2022)

Assessment of contaminants in sand production from petroleum wells offshore Sabah - Muhammad Shafiq Mat Shayuti; Suzalina Zainal; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Munawar Zaman Shahruddin; Nur Hidayati Othman; Nur Hashimah Alias; Tengku Amran Tengku Mohd; Rahida Wati Sharudin (Environmental Science and Pollution Research, 2022)

Multivariate geo-statistical perspective: evaluation of agricultural soil contaminated by industrial estate’s effluents - Muhammad Jamil; Ijaz Malook; Shafiq Ur Rehman; Muhammad Daud Khan; Muhammad Fayyaz; Muhammad Mudasar Aslam; Eui Shik Rha (Environmental Geochemistry and Health, 2022)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Exploring the effect of ultrasonic power, frequency, and load toward remediation of oil-contaminated beach and oilfield sands using ANOVA - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Nur Hidayati Othman; Nur Hashimah Alias (Environmental Science and Pollution Research, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

Correction to: influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Greenwash and green purchase behavior: an environmentally sustainable perspective - Irfan Hameed; Zeeshan Hyder; Muhammad Imran; Kashif Shafiq (Environment, Development and Sustainability, 2021)

Forecasting and modeling of atmospheric methane concentration - Shafiq Ur Rehman; Ijaz Husain; Muhammad Zaffar Hashmi; Elsayed Elsherbini Elashkar; Jameel Ahmad Khader; Mohammed Ageli (Arabian Journal of Geosciences, 2021)

Complete nucleotide sequence of a begomovirus associated with an alphasatellite and a betasatellite naturally infecting okra in Jordan - Nida’ M. Salem; Muhammad Shafiq Shahid; Ali Idris; Dina Hattab; Amany Abdeen (Archives of Virology, 2021)

Advances in Salt Tolerance of Some Major Fiber Crops Through Classical and Advanced Biotechnological Tools: A Review - Nudrat Aisha Akram; Fahad Shafiq; Muhammad Ashraf; Muhammad Iqbal; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2021)

Evidence that leaf curl disease of Malva sylvestris in Iran is associated with cotton leaf curl Gezira virus and associated betasatellite - Kaveh Bananej; Muhammad Shafiq Shahid; Muhammad Shafiq (Journal of Plant Pathology, 2021)

Depositional, diagenetic, and sequence stratigraphic constrains on reservoir characterization: a case study of middle Jurassic Samana Suk Formation, western Salt Range, Pakistan - Bilal Wadood; Mansoor Aziz; Junaid Ali; Nasar Khan; Jamal Wadood; Ahmad Khan; Muhammad Shafiq; Mohib Ullah (Journal of Sedimentary Environments, 2021)

A state-of-the-art review on wastewater treatment techniques: the effectiveness of adsorption method - Ruhma Rashid; Iqrash Shafiq; Parveen Akhter; Muhammad Javid Iqbal; Murid Hussain (Environmental Science and Pollution Research, 2021)

Microarray analysis of Arabidopsis thaliana exposed to single and mixed infections with Cucumber mosaic virus and turnip viruses - Aminallah Tahmasebi; Bahman Khahani; Elahe Tavakol; Alireza Afsharifar; Muhammad Shafiq Shahid (Physiology and Molecular Biology of Plants, 2021)

Effect of acetate, β-hydroxybutyrate and their interaction on lipogenic gene expression, triglyceride contents and lipid droplet formation in dairy cow mammary epithelial cells - Ilyas Ali; Chengmin Li; Lian Li; Meiqian Kuang; Muhammad Shafiq; Yiru Wang; Min Yang; Genlin Wang (In Vitro Cellular & Developmental Biology - Animal, 2021)

Interaction of watermelon chlorotic stunt virus with satellites - Muhammad Shafiq; Muhammad Naeem Sattar; Muhammad Shafiq Shahid; Abdullah M. Al-Sadi; Rob W. Briddon (Australasian Plant Pathology, 2021)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Impact assessment of urban development patterns on land surface temperature by using remote sensing techniques: a case study of Lahore, Faisalabad and Multan district - Muhammad Sajid Saleem; Sajid Rashid Ahmad; Shafiq-Ur-Rehman; Muhammad Asif Javed (Environmental Science and Pollution Research, 2020)

Evaluation of Diffusivity and Wettability of Crude Oil-Contaminated Sand from Offshore Petroleum Facility Prior to Remediation Process - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Nur Hashimah Alias; Nur Hidayati Othman; Suzalina Zainal (Water, Air, & Soil Pollution, 2020)

RLP, a bacteriophage of the family Podoviridae, rescues mice from bacteremia caused by multi-drug-resistant Pseudomonas aeruginosa - Iqbal Ahmad Alvi; Muhammad Asif; Rabia Tabassum; Rehan Aslam; Zaigham Abbas; Shafiq ur Rehman (Archives of Virology, 2020)

Foliar applied fullerol differentially improves salt tolerance in wheat through ion compartmentalization, osmotic adjustments and regulation of enzymatic antioxidants - Fahad Shafiq; Muhammad Iqbal; Muhammad Arslan Ashraf; Muhammad Ali (Physiology and Molecular Biology of Plants, 2020)

TAC1, an unclassified bacteriophage of the family Myoviridae infecting Acinetobacter baumannii with a large burst size and a short latent period - Muhammad Asif; Iqbal Ahmad Alvi; Rabia Tabassum; Shafiq Ur Rehman (Archives of Virology, 2020)

Seed Pre-treatment with Polyhydroxy Fullerene Nanoparticles Confer Salt Tolerance in Wheat Through Upregulation of H2O2 Neutralizing Enzymes and Phosphorus Uptake - Fahad Shafiq; Muhammad Iqbal; Muhammad Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2019)

Hesperetin Confers Neuroprotection by Regulating Nrf2/TLR4/NF-κB Signaling in an Aβ Mouse Model - Muhammad Ikram; Tahir Muhammad; Shafiq Ur Rehman; Amjad Khan; Min Gi Jo; Tahir Ali; Myeong Ok Kim (Molecular Neurobiology, 2019)

Progress in ultrasonic oil-contaminated sand cleaning: a fundamental review - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Putri Nadzrul Faizura Megat Khamaruddin; Nur Hidayati Othman (Environmental Science and Pollution Research, 2019)

Infection of Urtica incisa with chili leaf curl virus and tomato leaf curl betasatellite in Oman - Muhammad Shafiq Shahid; Amir Raza; Muhammad Shafiq; Abdullah M. Al-Sadi; Rob W. Briddon (Journal of Plant Pathology, 2019)

The Rep proteins encoded by alphasatellites restore expression of a transcriptionally silenced green fluorescent protein transgene in Nicotiana benthamiana - Qamar Abbas; Imran Amin; Shahid Mansoor; Muhammad Shafiq; Michael Wassenegger; Rob W. Briddon (VirusDisease, 2019)

Molecular characterization and clinical epidemiology of HCV in District Dir (Lower), Pakistan - Sami Ullah; Muhammad Akram Khan; Shafiq Ur Rahman; Imran Khan; Fazal Akbar; Anshu Babbar (VirusDisease, 2018)

Pesticide-induced oxidative stress and antioxidant responses in tomato (Solanum lycopersicum) seedlings - Shakirullah Khan Shakir; Shahid Irfan; Basreen Akhtar; Shafiq ur Rehman; Muhammad Khan Daud; Nadia Taimur; Azizullah Azizullah (Ecotoxicology, 2018)

Natural Dietary Supplementation of Anthocyanins via PI3K/Akt/Nrf2/HO-1 Pathways Mitigate Oxidative Stress, Neurodegeneration, and Memory Impairment in a Mouse Model of Alzheimer’s Disease - Tahir Ali; Taehyun Kim; Shafiq Ur Rehman; Muhammad Sohail Khan; Faiz Ul Amin; Mehtab Khan; Muhammad Ikram; Myeong Ok Kim (Molecular Neurobiology, 2018)

Impact of city effluents on water quality of Indus River: assessment of temporal and spatial variations in the southern region of Khyber Pakhtunkhwa, Pakistan - Ilham Khan; Azim Khan; Muhammad Sohail Khan; Shabnam Zafar; Asma Hameed; Shakeel Badshah; Shafiq Ur Rehman; Hidayat Ullah; Ghazala Yasmeen (Environmental Monitoring and Assessment, 2018)

PAAN135, a novel rhizospheric fungus associated with Cholistan desert grass Panicum antidotale, is a species of Saccharomycetales and a new source of cyclo-L-prolylglycine diketopiperazine - Faiz-ul-Hassan Nasim; Adeela Naureen; Muhammad Saleem; Naheed Riaz; Muhammad Shafiq Choudhary; Muhammad Ashraf (Symbiosis, 2018)

Aminolevulinic acid and nitric oxide regulate oxidative defense and secondary metabolisms in canola (Brassica napus L.) under drought stress - Nudrat Aisha Akram; Majid Iqbal; Atta Muhammad; Muhammad Ashraf; Fahad Al-Qurainy; Sidra Shafiq (Protoplasma, 2018)

Effective Bioremediation of Endocrine-Disrupting Phthalate Esters, Mediated by Bacillus Strains - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Farah Amin; Abid Ali Khaskheli; Shazia Bhurgri; Hassan Imran Afridi; Shafiq Ur Rahman (Water, Air, & Soil Pollution, 2017)

Pb-induced changes in roots of two cultivated rice cultivars grown in lead-contaminated soil mediated by smoke - Nazneen Akhtar; Sehresh Khan; Ijaz Malook; Shafiq Ur Rehman; Muhammad Jamil (Environmental Science and Pollution Research, 2017)

Modeling of Cr contamination in the agricultural lands of three villages near the leather industry in Kasur, Pakistan, using statistical and GIS techniques - Muhammad Shafiq; Tahira Shaukat; Aisha Nazir; Firdaus-e- Bareen (Environmental Monitoring and Assessment, 2017)

Chromium tolerance, oxidative stress response, morphological characteristics, and FTIR studies of phytopathogenic fungus Sclerotium rolfsii - Shahid Rafi; Amna Shoaib; Zoia Arshad Awan; Nayab Batool Rizvi; Nafisa; Muhammad Shafiq (Folia Microbiologica, 2017)

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

Synergistic effects of drought and ascorbic acid on growth, mineral nutrients and oxidative defense system in canola (Brassica napus L.) plants - Sidra Shafiq; Nudrat Aisha Akram; Muhammad Ashraf; Amara Arshad (Acta Physiologiae Plantarum, 2014)

A distinct strain of chickpea chlorotic dwarf virus (genus Mastrevirus, family Geminiviridae) identified in cotton plants affected by leaf curl disease - Muhammad Tariq Manzoor; Muhammad Ilyas; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid; Rob W. Briddon (Archives of Virology, 2014)

Deterministic and probabilistic seismic hazard analysis for Gwadar City, Pakistan - Shafiq Ur Rehman; Muhammad Khalid; Asif Ali; Abd El-aziz Khairy Abd El-Aal (Arabian Journal of Geosciences, 2013)

Complete nucleotide sequences of two begomoviruses infecting Madagascar periwinkle (Catharanthus roseus) from Pakistan - Muhammad Ilyas; Kiran Nawaz; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid (Archives of Virology, 2013)

An investigation of phenolic compounds from plant sources as trypsin inhibitors - Durre Shahwar; Muhammad Asam Raza; Shafiq-Ur-Rehman; Muhammad Athar Abbasi; Atta-Ur-Rahman (Natural Product Research, 2012)

Pure culture of Metarhizium anisopliae LHL07 reprograms soybean to higher growth and mitigates salt stress - Abdul Latif Khan; Muhammad Hamayun; Sumera Afzal Khan; Sang-Mo Kang; Zabta Khan Shinwari; Muhammad Kamran; Shafiq ur Rehman; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2012)